Carbonic anhydrase mimics for enhanced CO2 absorption in an amine-based capture solvent. Issue 1 (26th November 2015) - Kelsey, Rachael A.; Miller, David A.; Parkin, Sean R.; Liu, Kun; Remias, Joe E.; Yang, Yue; Lightstone, Felice C.; Liu, Kunlei; Lippert, Cameron A.; Odom, Susan A.
Abstract : Carbonic anhydrase converts CO2 to HCO3 − in physiological conditions, but in the highly basic amine-containing solutions used industrially for carbon capture, the enzyme does not function. Instead small molecule mimics can catalyze CO2 hydration. Abstract : Two new small-molecule enzyme mimics of carbonic anhydrase were prepared and characterized. These complexes contain the salen-like ligand bis(hydroxyphenyl)phenanthroline. This ligand is similar to the salen-type ligands previously incorporated into carbonic anhydrase mimics but contains no hydrolyzable imine groups and therefore serves as a promising ligand scaffold for the synthesis of a more robust CO2 hydration catalyst. These homogeneous catalysts were investigated for CO2 hydration in concentrated primary amine solutions through which a dilute CO2 (14%) fluid stream was flowed and showed exceptional activity for increased CO2 absorption rates.